Vauxhall Mirror, 1947 (London, 1947)
1947 1945-1951 "Vauxhall Mirror, 1947" [BW0128], 1947, Trades Union Congress This newspaper, containing news of workers' sports and social activities, was published by the Vauxhall Motors Recreation Club and the company's Welfare Department in Luton. After the reduction in leisure activities during the Second World War, sport and leisure activities increased during the 1950s. There was increased employer spending on educational and recreational programmes which were seen as good public relations, helping to build an image of corporate benevolence in the workplace and in the community, but also good for productivity and industrial relations.